Focused ion beam (FIB) prepared microtextured microneedle array capable of delivering drugs through punctured skin - Yan Zhang; Zhaoqiang Chen; Wendong Wu; Chonghai Xu (Scientific Reports)
Abstract Microtextured microneedles are tiny needle-like structures with micron-scale microtextures, and the drugs stored in the microtextures can be released after entering the skin to achieve the effect of precise drug delivery. In this study, the skin substitution model of Ogden’s hyperelastic model and the microneedle array and microtexture models with different geometrical parameters were selected to simulate and analyse the flow of the microtexture microneedle arrays penetrating the skin by the finite-element method, and the length of the microneedles was determined to be 200 μm, the width 160 μm, and the value of the gaps was determined to be 420 μm. A four-pronged cone was chosen as the shape of microneedles, and a rectangle was chosen as the shape of the drug-carrying microneedle. The initial microneedle arrays were prepared by wet etching using monocrystalline silicon as the material due to its high mechanical strength, stability and good biocompatibility. The sputtering yield, energy loss and material damage of single crystal silicon materials during focused ion beam (FIB) processing were calculated using Monte Carlo method and found to have optimum removal efficiency and processing accuracy at 30 keV ion beam voltage. After the initial microneedle arrays were prepared using wet etching, microtextures were prepared on the microneedles with 30° inclination and 45° inclination using FIB technique with processing parameters of 30 keV and 60 nA. Biocompatibility tests showed a cell survival rate of 99.42% for the cell set containing the microneedle array, indicating that the microneedle array was non-toxic to the cells. The viscosity and contact angle of 5-fluorouracil, triamcinolone acetonide and tacrolimus were examined and it was learnt that tacrolimus had the highest viscosity and the lowest contact angle and the configured solution was able to be more present in the microtexture and was more stable and less susceptible to loss. The experiments of drug-carrying skin puncture mice showed that the stained area of tacrolimus was brighter and more uniformly distributed, the stained area of microtextured microneedles was larger than that of ordinary microneedles by 70.52%, the drug-carrying area was larger than the average area of ordinary microneedles by 105.09%, and the drug-carrying effect of microtextured microneedles with a horizontal inclination angle of 30° was more effective.